Examination of optical soliton solutions for the perturbed Schrödinger-Hirota equation with anti-cubic law in the presence of spatiotemporal dispersion - Durmus, Selvi Altun; Ozdemir, Neslihan; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa (SPRINGER HEIDELBERG, 2024)
In the current paper, the perturbed Schr & ouml;dinger-Hirota equation having anti-cubic nonlinearity is analyzed with the aid of the new Kudryashov scheme. What distinguishes this article from other articles is that it not only attains multifold analytical solutions to the underresearched model but also verifies the impact of the anti-cubic law media on soliton attitude for the first time. The algorithmic rules and solution functions of the presented method have been controlled with symbolic algebraic software, and every outcome has been approved attentively. Then, the given method has been implemented on the model under consideration for the collective test objective. With the conventional norm approximation, the nonlinear partial differential structure of the model under consideration has been turned into the ordinary differential structure by performing the wave transmutation, and then the presented technique has been implemented into the ordinary differential structure of the proposed model. After this process, we have acquired a system of linear algebraic equations and their convenient solutions. Afterward, by attaining the proper solution sets, the soliton solutions of the given model, such as bright, W-shape-like, and dark soliton forms, have been arranged, and some chosen diagrammatic views have been presented.
Keywords: WAVE SOLUTIONS; MODEL; Physics